Namibia: Recent developments in agricultural research - Stads, Gert-Jan; Pholo, Motlalepula (International Food Policy Research Institute, 2011)
After attaining independence from South Africa in 1990, Namibia shifted the focus of its agricultural research and development (R&D) away from commercial landholders toward small-scale subsistence farmers. In the early 1990s, agricultural R&D investment and capacity levels rose rapidly (Beintema, Pardey, and Roseboom 1994), but levels have been somewhat erratic since 2000. In 2008, the country spent 94 million Namibian dollars or 22 million PPP dollars, down from a high of 132 million Namibian dollars or 31 million PPP dollars, all in 2005 constant prices (Figure 1, Table 1). Unless otherwise stated, financial data in this note are based on PPP exchange rates, which reflect the purchasing power of currencies more e ectively than do standard exchange rates because they compare the prices of a broader range of local—as opposed to internationally traded—goods and services.1 The total number of full-time equivalent (FTE) agricultural R&D staff active in Namibia increased slightly during 2001-08, from 66 to 70, despite yearly uctuations (Figure 2).